Strength and conditioning for professional boxing: Recommendations for physical preparation - Ruddock, A. D.; Wilson, D. C.; Thompson, S. W.; Hembrough, D.; Winter, E. M. (Strength and Conditioning Journal, 2016)
Professional boxing is a popular pan-global sport that attracts considerable interest and revenue. It is a high-intensity sport that requires a range of well-adapted physiological characteristics as likely prerequisites for successful performance. Serious consideration has been given to medical aspects and potential health risks from partaking in training and competition. However, there are no comprehensive sources of applied sport science research in the preparation of professional boxers for competition. In this review, we present research from physiology and strength and conditioning to form a knowledge base for those involved in preparing professional boxers for competition.